Circular RNA PVT1 Regulates Cell Proliferation, Migration, and Apoptosis by Stabilizing c-Myc and Downstream Target CXCR4 Expression in Acute Myeloid Leukemia - Xian Fu Sheng; Li Li Hong; Lei Fan; Kai-Li Chen; Jie Mu; Si Yu Shen; Hai-Feng Zhuang (Turkish Journal of Hematology, 2023)
Objective: This study aimed to investigate the role and mechanism of circular RNA PVT1 (circPVT1) in patients with acute myeloid leukemia (AML). Materials and Methods: The expression of circPVT1 in 23 patients with de novo AML (not acute promyelocytic leukemia, not APL) and cell lines were detected by RT-qPCR. Loss of function assays were carried out to explore the influence of silenced circPVT1 on the proliferation, migration, and apoptosis in the THP-1 cell line. CCK-8 assays, transwell assays, and annexin V/PI staining assays were performed to assess proliferation, migration, and apoptosis, respectively. Results: CircPVT1 was highly expressed in AML patients and myeloid cell lines compared to healthy controls. Higher expression of circPVT1 was related to shorter overall survival (OS) and relapse-free survival (RFS) in AML patients. Cell viability and migration were inhibited and apoptosis was increased when circPVT1 was knocked down in THP-1 cells. Knockdown of circPVT1 resulted in marked suppression of c-Myc protein with no significant change in mRNA levels. We also found that circPVT1 knockdown markedly increased the phosphorylation of c-Myc Thr-58, which was responsible for c-Myc degradation. Silencing of c-Myc caused a significant decrease in CXCR4 mRNA and protein expression, whereas the overexpression of c-Myc caused the opposite result, suggesting that CXCR4 is a target molecule of c-Myc. Finally, we found that overexpression of c-Myc could partially reverse circPVT1 knockdown-induced anti-tumor effects on THP-1 cells in vitro. Conclusion: Our findings showed that circPVT1 was highly expressed in AML patients and was related to shorter OS and RFS. CircPVT1 may exert an oncogenic effect in THP-1 cells by stabilizing c-Myc protein expression and downstream target CXCR4 expression. These data indicate that circPVT1 may be a promising therapeutic target for AML.